UJI EFEK ANALGETIK EKSTRAK RUMPUT TEKI (CYPERUS ROTUNDUS L.) PADA TIKUS PUTIH JANTAN GALUR WISTAR (RATTUS NOVERGICUS) - Pandey, Putri Virgie; Bodhi, Widdhi; Yudistira, Adithya (PHARMACON, 2013)
Pain is defined as a sensory and emotional experience that is not associated with tissuedamage. Nut grass (Cyperus rotundus L.) is traditionally used as a pain reliever. Theobjectives of this research were to find out analgesic effect of nut grass extract withconcentration 3,15 g/KgBB, 6,3 g/KgBB and 12,6 g/KgBB on white male wistar. The subjectin this research were 15 white male wistar which divided into 5 groups, each group consist of3 white male wistar. Negative control group were administered with aquadest, positivecontrol group were administered with paracetamol, and experiment groups were administeredwith nut grass extract. Analgesic test were examined by giving pain stimulation to treatedanimals, such as 65Â°C heat stimulation. The response which observed were rats licking feetor jumping response. The observation was conducted for 1 minute.Observations wereconducted before extract administration, then at 30, 60, 90 and 120 minutes afteradministered. The results shows thatnut grass extract with concentration 3,15 g/KgBB, 6,3g/KgBB and 12,6 g/KgBB possess analgesic effect on white male wistar, especiallyconcentration 6,3 g/KgBB.Keywords: analgesic, nut grass extract, pain